1,4a-Dimethyl-6-methylene-5-(5,5,6,6-tetracyano-2-methylcyclohex-2-enylmethyl)decahydronaphthalene-1-carboxylic acid: a trans-communic acid derivative - Jean-Claude Daran; Ahmed Benharref; My Youssef Ait Itto; Aziz Auhmani; Nezha Rejouani (Acta Crystallographica Section E, 2008)
In the search for cancer chemopreventive agents, we have studied the Diels–Alder reaction of trans-communic acid with tetracyanoethylene in the presence of SiO2 as catalyst. The title cycloadduct, C26H30N4O2, was obtained in 75% yield. The molecules are arranged in pairs through O—H...O hydrogen bonds, forming an R22(8) ring motif. Both the fused cyclohexyl rings adopt a chair conformation, whereas the nonfused ring adopts a half-chair conformation.